Effect of salt concentration on the properties of electrolyzed reducing water (ERW) and electrolyzed oxidizing water (EOW): an empirical correlation study - Prasakti, Laras; Yogihaz, Billy Dion; Subekti, Lukman; Sujarwo, Anton; Prasetya, Agus (Jurnal Rekayasa Proses, 2022)
This research aimed to examine the effect of NaCl concentration on the pH and Oxidation Reduction Potential (ORP) values of both EOW and ERW products. The experiment was conducted using distilled water. The electrolysis apparatus consisted of anode and cathode chambers. The chambers were connected by a tube filled with a cotton (or a fabric). Both electrodes (anode and cathode) were made of titanium and formed as a spiral. Electrolysis was performed for 780 minutes, and the pH and ORP values of both EOW and ERW were measured every time. Sodium chloride concentration was varied for 0, 100, and 200 ppm. Experimental results revealed that the higher the NaCl concentration, the higher ERW’s pH rise and the lower the EOW’s pH. Similar results were found for ORP. ERW’s ORP was lowered while EOW’s ORP rose with the increase in NaCl concentration. This study could also generate a mathematical model that correlates pH and time during the electrolysis process. The model was developed by connecting with a simple polynomial. A similar approach was used to develop the model that correlates pH and ORP value.